Research on Resources Configuration of Access Service - Jie Yin; Wenjun Shen (Dianxin kexue)
Based on a distinctive classification method for telecom business, the definition and resource configuration process of access service was discussed in details. Then an E-R model for resources and access services was proposed. Also, some opinions of access methods and coverage which are very important in service configuration process were showed.